7\6-1\6:2\3
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Lời giải chi tiết:
3 + 4 > 6 | 6 + 1 > 6 | 5 + 1 = 6 |
3 + 4 = 7 | 5 + 2 > 6 | 7 – 5 > 3 |
7 – 4 < 4 | 7 – 2 = 5 | 7 – 6 = 1 |
Lời giải chi tiết:
7 > 6 | 2 < 5 | 7 > 3 | 6 = 6 |
7 > 4 | 5 < 7 | 3 > 1 | 6 < 7 |
7 > 2 | 2 < 7 | 7 > 1 | 7 = 7 |
\(\dfrac{2}{5}+\dfrac{2}{3}+\dfrac{2}{4}\)
= \(\dfrac{24}{60}\) + \(\dfrac{40}{60}\) + \(\dfrac{30}{60}\)
= \(\dfrac{64}{60}\) + \(\dfrac{30}{60}\)
= \(\dfrac{47}{30}\)
\(\dfrac{2}{6}+\dfrac{3}{12}\)
= \(\dfrac{4}{12}\) + \(\dfrac{3}{12}\)
= \(\dfrac{7}{12}\)
\(\dfrac{5}{6}\) + \(\dfrac{1}{3}\)
= \(\dfrac{5}{6}\) + \(\dfrac{2}{6}\)
= \(\dfrac{7}{6}\)
\(\dfrac{1}{3}\) + \(\dfrac{5}{12}\) + \(\dfrac{5}{6}\)
= \(\dfrac{4}{12}\) + \(\dfrac{5}{12}\) + \(\dfrac{10}{12}\)
= \(\dfrac{9}{12}\) + \(\dfrac{10}{12}\)
= \(\dfrac{19}{12}\)
\(\dfrac{5}{8}\) + \(\dfrac{4}{7}\)
= \(\dfrac{35}{56}\) + \(\dfrac{32}{56}\)
= \(\dfrac{67}{56}\)
\(\dfrac{7}{3}\) + \(\dfrac{8}{7}\)
= \(\dfrac{49}{21}\) + \(\dfrac{24}{21}\)
= \(\dfrac{73}{21}\)
\(\dfrac{1}{5}+\dfrac{5}{35}\)
= \(\dfrac{7}{35}\) + \(\dfrac{5}{35}\)
= \(\dfrac{12}{35}\)
5: \(=3-\dfrac{1}{4}+\dfrac{2}{3}-5+\dfrac{1}{3}+\dfrac{6}{5}-6+\dfrac{7}{4}-\dfrac{3}{2}\)
\(=3-5-6+\dfrac{-1}{4}+\dfrac{7}{4}+\dfrac{2}{3}+\dfrac{1}{3}+\dfrac{6}{5}-\dfrac{3}{2}\)
\(=-8+\dfrac{3}{2}+1+\dfrac{-3}{10}\)
\(=-7+\dfrac{15-3}{10}=-7+\dfrac{6}{5}=-\dfrac{29}{5}\)
6: \(=6-\dfrac{2}{3}+\dfrac{1}{2}-5-\dfrac{5}{3}+\dfrac{3}{2}-3+\dfrac{7}{3}-\dfrac{5}{2}\)
\(=6-5-3-\dfrac{2}{3}-\dfrac{5}{3}+\dfrac{7}{3}+\dfrac{1}{2}+\dfrac{3}{2}-\dfrac{5}{2}\)
\(=-2-\dfrac{1}{2}=-\dfrac{5}{2}\)
7: \(=\dfrac{5}{3}-\dfrac{3}{7}+9-2-\dfrac{5}{7}+\dfrac{2}{3}+\dfrac{8}{7}-\dfrac{4}{3}-10\)
\(=9-2-10+\dfrac{5}{3}+\dfrac{2}{3}-\dfrac{4}{3}+\dfrac{-3}{7}-\dfrac{5}{7}+\dfrac{8}{7}\)
=-3+1
=-2
8: \(=8-\dfrac{9}{4}+\dfrac{2}{7}+6+\dfrac{3}{7}-\dfrac{5}{4}-3-\dfrac{2}{4}+\dfrac{9}{7}\)
\(=8+6-3+\dfrac{2}{7}+\dfrac{3}{7}+\dfrac{9}{7}-1-\dfrac{2}{4}\)
\(=11+2-1-\dfrac{1}{2}\)
=11+1/2
=11,5
\(\dfrac{8}{9}:\dfrac{3}{7}=\dfrac{56}{27}\\ \dfrac{8}{9}+\dfrac{2}{5}=\dfrac{58}{45}\\ \dfrac{7}{8}-\dfrac{1}{3}=\dfrac{13}{24}\\ \dfrac{3}{10}\times\dfrac{1}{6}=\dfrac{1}{20}\\ 1\dfrac{2}{7}+6\dfrac{5}{6}=\dfrac{9}{7}+\dfrac{41}{6}=\dfrac{341}{42}\\ 5\dfrac{3}{4}-\dfrac{1}{5}=\dfrac{23}{4}-\dfrac{1}{5}=\dfrac{111}{20}\\ 6\dfrac{2}{9}:4\dfrac{7}{10}=\dfrac{56}{9}:\dfrac{47}{10}=\dfrac{560}{423}\\ \dfrac{5}{3}+\dfrac{3}{2}-\dfrac{7}{6}=2\)
Lời giải chi tiết:
9 + 1 = 10 | 8 + 2 = 10 | 7 + 3 = 10 | 6 + 4 = 10 |
1 + 9 = 10 | 2 + 8 = 10 | 3 + 7 = 10 | 4 + 6 = 10 |
9 – 1 = 8 | 8 – 2 = 6 | 7 – 3 = 4 | 6 – 4 = 2 |
9 – 9 = 0 | 8 – 8 = 0 | 7 – 7 = 0 | 6 – 6 = 0 |
Lời giải chi tiết:
5 + 4 = 9 | 6 + 3 = 9 | 7 + 2 = 9 | 1 + 8 = 9 |
5 + 3 + 1 = 9 | 6 + 2 + 1 = 9 | 7 + 1 + 1 = 9 | 1 + 2 + 6 = 9 |
5 + 2 + 2 = 9 | 6 + 3 + 0 = 9 | 7 + 0 + 2 = 9 | 1 + 5 + 3 = 9 |
5+4=9 | 6+3=9 | 7+2=9 | 1+8=9 |
5+3+1=9 | 6+2+1=9 | 7+1+1=9 | 1+2+6=9 |
5+2+2=9 | 6+3+0=9 | 7+0+2=9 | 1+5+3=9 |
( 1 + 1 +1 ) ! = 6
2 + 2+ 2 = 6
3.3-3 = 6
5+(5:5) = 6
6+6-6 = 6
7- ( 7 : 7) = 6
2 + 2 + 2 = 6
3 x 3 - 3 = 6
5 : 5 + 5 = 6
6 x 6 : 6 = 6
7 - 7 : 7 = 6